Maternal Parity and Onset of Lactation on Postpartum Mothers - Frieska Piesesha; Windhu Purnomo; Roedi Irawan (Health Notions, 2018)
Onset of lactation is one of indicators of lactogenesis stage II which is the important phase in infants breastfeeding. Breastfeeding is important as it gives many health benefits for both mother and babies. The early initiation of breastfeeding is not always going smooth as sometimes mothers or babies experience various difficulties that complicate the lactation process, especially in primipara women with less knowledge of lactation. Those obstacles and difficulties will influence the practice of breastfeeding which may lead to delay onset of lactation. Thus, this study was conducted to identify the onset of lactation and analyze parity factor on postpartum mothers in DKT hospital in Gubeng Pojok, Surabaya, East Java. It was an observational analytic study with prospective cohort design. 50 respondents were randomly selected using systematic random sampling. Regression logistic showed a correlation between parity and onset of lactation (p = 0.024; RR = 7.277), in which primipara mothers were 7.277 times more likely to have delay onset of laction than multipara mothers. It was concluded that maternal parity associated with onset of lactation on postpartum mothers. Keywords: Parity, Onset of lactation, Postpartum